BIOCHEMICALLY ASSESSED PATHOLOGICAL ACTIVITY OF ORAL CANDIDA IN DENTURE AND NON DENTURE WEARERS - Ghani, Fazal; Chughtai, Muhammad Ali; Shah, Syed Akram (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: ° Results: Conclusion: Not-with-standing the varying effect of other variables, denture-wearing significantly enhanced pathogenic activity of oral candida. The importance of meticulous oral and denture hygiene maintenance and rest to denture-supporting tissues is re-emphasized. Pathological candida activity was seen both in DWs and NDWs. However, it was significantly higher in DWs (p value = 0.00) with mean pH decrease of 1.9 as compared to 0.8 in NDWs. Except age, the effect of gender, socioeconomic status, medications, oral hygiene maintenance on the oral candida activity was insignificant both within and between groups. C. The influence of age, gender, socioeconomic status, smoking habits, medication-use, oral-hygiene maintenance method, denture-plaque level, and level of salivary function was also investigated. A Cross Sectional, Comparative study during March-September 2007 was conducted at Khyber College of Dentistry Peshawar and Zoology Department, University of Peshawar (Pakistan).Using a structured proforma, data were collected from 100 subjects (50 DWs and 50 NDWs). Stimulated salivary samples were collected from each subject. One ml of standard dilution saliva was mixed with 4 ml sterile liquid candida-selective medium. The extent of candida activity was then determined, biochemically, through change in pH of the medium 24 hrs after inoculation and incubation at 37 To assess the candida activity through recording pH changes in candida selective medium inoculated with standardized dilution salivary samples obtained from dentures wearers and non denture wearers.